Getting to Know Ovarian Cancer Ascites: Opportunities for Targeted Therapy-Based Translational Research - Ahmed, Nuzhat; Stenvers, Kaye (Frontiers in Oncology, 2013)
More than one third of ovarian cancer patients present with ascites at diagnosis, and almost all have ascites at recurrence. The presence of ascites correlates with the peritoneal spread of ovarian cancer and is associated with poor disease prognosis. Malignant ascites acts as a reservoir of a complex mixture of soluble factors and cellular components which provide a pro-inflammatory and tumor-promoting microenvironment for the tumor cells. Subpopulations of these tumor cells exhibit cancer stem-like phenotypes, possess enhanced resistance to therapies and the capacity for distal metastatic spread and recurrent disease. Thus, ascites-derived malignant cells and the ascites microenvironment represent a major source of morbidity and mortality for ovarian cancer patients. This review focuses on recent advances in our understanding of the molecular, cellular, and functional characteristics of the cellular populations within ascites and discusses their contributions to ovarian cancer metastasis, chemoresistance and recurrence. We highlight in particular recent translational findings which have used primary ascites-derived tumor cells as a tool to understand the pathogenesis of the disease, yielding new insights and targets for therapeutic manipulation.